2007
DOI: 10.1128/cvi.00339-07
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Serological Immune Responses to Foot-and-Mouth Disease Vaccine by a Supplement Made of Extract of Cochinchina Momordica Seeds

Abstract: Foot-and-mouth disease (FMD) is a highly contagious disease affecting cloven-hoofed animals. Vaccination against FMD is a routine practice in many countries where the disease is endemic. This study was designed first to investigate the extract of the seeds of Momordica cochinchinensis (Lour.) Spreng. (ECMS) for its adjuvant effect on vaccination of inactivated FMDV antigens in a guinea pig model and then to evaluate the supplement of ECMS in oil-emulsified FMD vaccines for its immunopotentiation in pigs. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…In further studies, the biochemical and molecular analyses will be performed to explain additional mechanisms of how the MC could prevent such adverse effects. The protective tissue damage effect demonstrated in this study is a phytotherapeutic property of MC extract besides other pharmacological properties shown in previous reports (Zheng et al;Jung et al, 2013aJung et al, , 2013bLiu et al;Chuethong et al;Tien et al;Kang et al;Tsoi et al;Xiao et al, 2007Xiao et al, , 2009Rajput et al, 2007Rajput et al, , 2010. Moreover, MC extract indeed did not affect any male reproductive parameters including testicular histology as compared to the control.…”
Section: Discussionmentioning
confidence: 48%
“…In further studies, the biochemical and molecular analyses will be performed to explain additional mechanisms of how the MC could prevent such adverse effects. The protective tissue damage effect demonstrated in this study is a phytotherapeutic property of MC extract besides other pharmacological properties shown in previous reports (Zheng et al;Jung et al, 2013aJung et al, , 2013bLiu et al;Chuethong et al;Tien et al;Kang et al;Tsoi et al;Xiao et al, 2007Xiao et al, , 2009Rajput et al, 2007Rajput et al, , 2010. Moreover, MC extract indeed did not affect any male reproductive parameters including testicular histology as compared to the control.…”
Section: Discussionmentioning
confidence: 48%
“…Additionally, both CEA and SCC are known to be typical tumour‐related antigens (TAAs) in oesophageal tumourigenesis . Interleukin‐6 (IL‐6) and macrophage inhibitory factor 1 (MIC‐1) are also extensively regarded as malignant biomarkers of ESCC . Accordingly, we evaluated the CEA, SCC, IL‐6, and MIC‐1 content in the serum of the mice.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Gerber reported that Quil A, in combination with oil as an adjuvant, promoted greater immune responses in pigs immunized against pseudorabies virus, in guinea pigs immunized against canine parvovirus, and in cats immunized against feline infectious virus (33), Martinez-Fernandez et al found that an oil emulsion containing Quil A increased the immune responses induced by Fh12 fatty acid-binding protein of Fasciola hepatica in sheep (34), and Xiao et al observed that supplements of saponins such as Quil A and extract from the seeds of Momordica cochinchinensis (Lour.) Spreng in FMD vaccines significantly enhanced immune responses in pigs (29,35). The synergism between RO and GS-R may be explained by the depot effect of oil emulsion, which slowly releases antigens at the injection site in combination with the immunostimulating effect created by GS-R. Figure 3 showed that serum IgG levels progressively declined but RO/GS-R reduced the rate of the decline.…”
Section: Discussionmentioning
confidence: 96%